Assessment of cardiorespiratory function in adolescent athletes affected by COVID-19: a comparative analysis - Tamara Stojmenović; Dragutin Stojmenović; Tijana Prodanović; Nikola Prodanović; Andrijana Kostić; Jelena Ceković Djordjevic; Suzana Živojinović (IP Iermakov S.S., 2024)
Background and Study Aim. Given the global spread of COVID-19 and its profound effects on public health, understanding its impact on the physical health and performance of young athletes is crucial for developing guidelines to support their recovery and well-being. The goal of this research was to assess the impact of the COVID-19 infection and possible consequences on the functional abilities of schoolchild athletes, and determine whether there are differences compared to their peers who did not suffer the infection. Material and Methods. This study involved 100 teenagers (median age 15.7±1.167), who engage in two different sports (basketball and soccer), divided into two groups. The first group comprised young athletes (n=53, age 15.79±1.854) who had contracted COVID-19 and underwent 14 days of home isolation. The second group consisted of healthy child athletes (n=47, age 15.60±1.313). Participants underwent a comprehensive pre-participation sports medical examination, which included a cardiopulmonary exercise test (CPET) on a treadmill. CPET assessed various physiological parameters: maximum oxygen consumption (VO2max); heart rates at the first and second ventilatory thresholds (HR at VT1 and HR at VT2); respiratory exchange ratio (RER); maximal pulmonary ventilation (VEmax); ventilatory efficiency (VE/VCO2); oxygen pulse (O2/HR); maximum heart rate (HRmax); three-minute heart rate recovery; and potential electrocardiographic changes. Results. The results indicate that COVID-19 infection has led to statistically significant impairments in the cardiorespiratory functions of child athletes. Notably, there were significant reductions in maximum oxygen consumption (VO2max), maximal pulmonary ventilation (VEmax), oxygen pulse (O2/HR), as well as heart rates at the first ventilatory threshold (HR at VT1), maximum heart rate (HRmax), and heart rate recovery following maximal effort, all demonstrating p-values less than 0.05. Conclusions. The assessed parameters demonstrated that the functions were statistically significantly impaired in child athletes who had recovered from COVID-19 compared to their healthy peers of the same age. However, the infection appeared to have a minimal impact on heart rate variability at ventilatory thresholds. These findings offer valuable insights for coaches and sports medicine physicians in adjusting training programs and supporting the rehabilitation process for young adolescent athletes resuming their training after recovering from COVID-19.